Comparative study of muller's maneuver and dexmedetomidine-induced sleep endoscopy in snoring adults - Jalil, Suhaili Abdul (2016)
Introduction Sleep-disordered breathing (SDB) comprises a wide spectrum of sleep-related breathing abnormalities from simple snorer at the one end and obstructive sleep apnoea/hypopnea syndrome (OSAHS) at the other end. It is characterized by repetitive partial or complete collapse of the upper airway during sleep, resulting in intermittent cessations of breathing (apnoeas) and reduction in airflow (hypopneas) despite on-going respiratory effort. Flexible nasopharyngolaryngoscope (FNPLS) can identify and quantify the site and degree of obstruction that caused the snoring. However, we normally evaluate the patient when he or she is awake and in erect position, whereas snoring occurs when patient is in supine and sleeping. The endoscopic findings during awake endoscopy may not accurate to conclude the site responsible for the production of snoring. Sleep endoscopy in the naturally asleep patient is a diagnostic method permits the examiner to better determine the site that is responsible for the production of snoring. The drug used is Dexmedetomidine with or without Midazolam. This can be beneficial for the choice of the different and most appropriate treatment options for optimal benefits to the patients. Objective To compare awake endoscopy (Muller’s maneuver) and drug-induced sleep endoscopy (DISE) findings in snoring individuals.Study design A cross sectional study was performed on patients aged more than 18 years old, with symptom of snoring planned for elective adenotonsillectomy and able to co-operate for FNPLS examination in Hospital Universiti Sains Malaysia. Methodology The consented patients who fulfilled the criterias were subjected to FNPLS with Muller’s maneuver at ORL-HNS Clinic, HUSM. After that, patients were admitted to ward one day prior to elective adenotonsillectomy surgery. Pre-operative assessment was done to assess whether patients were suitable and safe for Dexmedetomidineinduced sleep endoscopy. Patients were induced with the drug prior to intubation. FNPLS was repeated once patients reached sleep state based on bispectral index scoring system (BISS) score. Result A total of 15 patients with symptom of snoring participated in this study. Sixty-seven percent of them are male. All patients showed only one level airway obstruction which is at retropalatal level. Sixty percent have concentric type and 40% have lateral type of airway obstruction during Muller’s maneuver and during DISE, the configuration of airway obstruction was 80% and 20% respectively. During Muller’s maneuver, only 33% of patients showed grade 1 (50-75%) of airway obstruction and 67% showed grade 0 (<50%) at retropalatal level. However, during DISE, 67% and 33% of patients showed grade 1 and grade 2 (>75%) of airway obstruction respectively. All patients showedgrade 0 at retrolingual level during both procedures. Our study showed that there was poor agreement between Muller’s maneuver and DISE according to its degree and configuration of airway obstruction with ICC value was 0.14. Twenty percent of patients showed changes in the configuration of airway obstruction. Conclusion The degree of airway obstruction during DISE was more severe compared with the Muller’s maneuver. There was different in configuration of airway obstruction observed between these 2 procedures. DISE permits better evaluation of the degree and level of airway obstruction.